A statistical study of railway safety in China and Japan 1990–2020. (September 2022) - Cao, Yuan; An, Yuntong; Su, Shuai; Xie, Guo; Sun, Yongkui
Abstract: Safety is the precondition and guarantee of railway development. However, due to equipment failure, poor management, misoperation and so on, accidents on the railway occur from time to time. China and Japan, as leading countries in Railway Technology in the world, have done a lot of work in accident prevention and safety. Through the collection and comparison of transport data and typical casualty cases in China and Japan, this paper summarizes the main causes of accidents and the experience of accident prevention in the two countries. And further, puts forward suggestions for preventing accidents and large-scale casualty.